# 1.1 Exponents  (Page 2/2)

 Page 2 / 2

${a}^{0}=1$ , $\left(a\ne 0\right)$

For example, ${x}^{0}=1\text{and}\left(\text{1,000,000}{\right)}^{0}=1$ .

Note that the base must be a non-zero value. 0 0 is called an indeterminate number, and has no value. This is because 0 0 = 0/0. If one considers 0 = 0 × n (where n can be any number) then it follows that 0/0 = n , where n can be any number – meaning the value of 0/0 cannot be determined.

## Examples: application using exponential law 1

1. ${\text{16}}^{0}=1$
2. $\text{16}{a}^{0}=\text{16}$
3. $\left(\text{16}+a{\right)}^{0}=1$
4. $\left(-\text{16}{\right)}^{0}=1$
5. $-{\text{16}}^{0}=-1$

## Exponential law 2

Our definition of exponential notation shows that:

${a}^{m}×{a}^{n}={a}^{m+n}$

That is:

${a}^{m}\cdot {a}^{n}=1\cdot a\cdot \dots \cdot a$  ( m times) $\cdot 1\cdot a\cdot \dots \cdot \text{a}$   ( n times)

$=1\cdot a\cdot \dots \cdot a\text{}$     ( m + n times)

$={\text{a}}^{m+n}$

For example:

$\begin{array}{}{2}^{7}\cdot {2}^{3}=\left(2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\right)\text{}\left(2\cdot 2\cdot 2\right)\\ ={2}^{\text{10}}\\ ={2}^{7+3}\end{array}$

This simple law illustrates the reason exponentials were originally invented. In the days before calculators, all multiplication had to be done by hand with a pencil and a pad of paper. Multiplication takes a very long time to do and is very tedious. Adding numbers, however, is easy and quick. This law says that adding the exponents of two exponential numbers (of the same base) is the same as multiplying the two numbers together. This means that, for certain numbers, there is no need to actually multiply the numbers together in order to find their multiple. This saved mathematicians a lot of time.

## Examples: application using exponential law 2

1. ${x}^{2}\cdot {x}^{5}={\text{x}}^{7}$
2. ${2x}^{3}y\cdot {5x}^{2}{y}^{7}=\text{10}{x}^{5}{y}^{8}$
3. ${2}^{3}\cdot {2}^{4}={2}^{7}$    (Note that the base (2) stays the same.)
4. $3\cdot {3}^{2a}\cdot {3}^{2}={3}^{2a+3}$

## Exponential law 3

${a}^{m}÷{a}^{n}={a}^{m-n}$

We know from Law 2 that ${a}^{m+n}$ is base a multiplied by itself m times plus a multiplied by itself n times. Law 3 extends this to the case where an exponent is negative.

$\frac{{a}^{m}}{{a}^{n}}=\frac{a\cdot a\cdot a\cdots \cdot a}{a\cdot a\cdot a\cdots \cdot a}$ $\frac{\left(m\text{times}\right)}{\left(n\text{times}\right)}$

By factoring out ${a}^{n}$ from both numerator and denominator, we are left with

$=\frac{a\cdot a\cdot a\cdots \cdot a}{a\cdot a\cdot a\cdots \cdot a}$ $\frac{\left(m\text{times}\right)}{\left(n\text{times}\right)}$ $\frac{-a\cdot a\cdot a\cdots \cdot a}{-a\cdot a\cdot a\cdots \cdot a}$ $\frac{\left(n\text{times}\right)}{\left(n\text{times}\right)}$

$=a\cdot a\cdot a\cdots \cdot a$    ( m n times)

$={a}^{m-n}$

For example,

$\begin{array}{}{2}^{7}÷{2}^{3}=\frac{2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2}{2\cdot 2\cdot 2}\\ =2\cdot 2\cdot 2\cdot 2\\ ={2}^{4}\\ ={2}^{7-3}\end{array}$

## Examples: exponential law 3

1. $\frac{{a}^{6}}{{a}^{2}}={a}^{6-2}={a}^{4}$
2. $\frac{{3}^{2}}{{3}^{6}}={3}^{2-6}={3}^{-4}=\frac{1}{{3}^{4}}$    (Always give the final answer with a positive index)
3. $\frac{\text{32}{a}^{2}}{{4a}^{8}}={8a}^{-6}=\frac{8}{{a}^{6}}$
4. $\frac{{a}^{3x}}{{a}^{4}}={a}^{3x-4}$

## Exponential law 4

${a}^{-n}=\frac{1}{{a}^{n}},a\ne 0$

Our definition of exponential notation for a negative exponent shows that

${a}^{-n}=1÷a÷\cdots ÷a$    ( n times)

$=\frac{1}{1\cdot a\cdot \cdots \cdot a}$ $\frac{}{\left(n\text{times}\right)}$

$=\frac{1}{{a}^{n}}$

The minus sign in the exponent is just another way of writing that the whole exponential number is to be divided instead of multiplied.

For example, starting with Law 3, take the case of ${a}^{m-n}$ , but where  n>m :

$\begin{array}{}{2}^{2-9}=\frac{{2}^{2}}{{2}^{9}}\\ =\frac{2\cdot 2}{2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2}\\ =\frac{1}{2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2}\\ =\frac{1}{{2}^{7}}\\ ={2}^{-7}\end{array}$

## Examples: exponential law 4

1. ${2}^{-2}=\frac{1}{{2}^{2}}=\frac{1}{4}$
2. $\frac{{2}^{-2}}{{3}^{2}}=\frac{1}{{2}^{2}\cdot {3}^{2}}=\frac{1}{\text{36}}$
3. ${\left(\frac{2}{3}\right)}^{-3}={\left(\frac{3}{2}\right)}^{3}=\frac{\text{27}}{8}$
4. $\frac{m}{{n}^{-4}}={\text{mn}}^{4}$
5. $\frac{{a}^{-3}\cdot {x}^{4}}{{a}^{5}\cdot {x}^{-2}}=\frac{{x}^{4}\cdot {x}^{2}}{{a}^{3}\cdot {a}^{5}}=\frac{{x}^{6}}{{a}^{8}}$

## Exponential law 5

$\left(\text{ab}{\right)}^{n}={a}^{n}{b}^{n}$

The order in which two real numbers are multiplied together does not matter.

Therefore,

$\left(\text{ab}{\right)}^{n}=a\cdot b\cdot a\cdot b\cdot a\cdot b\cdot \cdots \cdot a\cdot b$     ( n times)

$=a\cdot a\cdot \dots \cdot a$  ( n times) $\cdot b\cdot b\cdot \dots \cdot b$  ( n times)

$={a}^{n}{b}^{n}$

For example:

$\begin{array}{}2\cdot {3}^{4}=\left(2\cdot 3\right)\cdot \left(2\cdot 3\right)\cdot \left(2\cdot 3\right)\cdot \left(2\cdot 3\right)\\ =\left(2\cdot 2\cdot 2\cdot 2\right)\cdot \left(3\cdot 3\cdot 3\cdot 3\right)\\ ={2}^{4}\cdot {3}^{4}\\ ={2}^{4}{3}^{4}\end{array}$

## Examples: exponential law 5

1. $\left({2x}^{2}y{\right)}^{3}={2}^{3}{x}^{2×3}{y}^{3}={8x}^{6}{y}^{3}$
2. $\left(\frac{7a}{{b}^{3}}\right){}^{2}=\frac{\text{49}{a}^{2}}{{b}^{6}}$
3. $\left({5a}^{n-4}{\right)}^{3}=\text{125}{a}^{3n-\text{12}}$

## Exponential law 6

$\left({a}^{m}{\right)}^{n}={a}^{\text{mn}}$

We can find the exponential of an exponential just as well as we can for a number, because an exponential is a real number.

$\left({a}^{m}{\right)}^{n}={a}^{m}\cdot {a}^{m}\cdot {a}^{m}\cdot \dots \cdot {a}^{m}$     ( n times)

$=a\cdot a\cdot \dots \cdot \text{a}$       ( m × n times)

$={\text{a}}^{\text{mn}}$

For example:

$\begin{array}{}\left({2}^{2}{\right)}^{3}=\left({2}^{2}\right)\cdot \left({2}^{2}\right)\cdot \left({2}^{2}\right)\\ =\left(2\cdot 2\right)\cdot \left(2\cdot 2\right)\cdot \left(2\cdot 2\right)\\ ={2}^{6}\\ ={2}^{2×3}\end{array}$

## Examples: exponential law 6

1. $\left({x}^{3}{\right)}^{4}={x}^{\text{12}}$
2. $\left[\left({a}^{4}{\right)}^{3}{\right]}^{2}={a}^{\text{24}}$
3. $\left({3}^{n+3}{\right)}^{2}={3}^{2n+6}$

## Module review exercises

Write the following examples using exponential notation.

$4\cdot 4$

4 2

$\text{12}\cdot \text{12}$

12 2

$9\cdot 9\cdot 9\cdot 9$

9 4

$\text{10}\cdot \text{10}\cdot \text{10}\cdot \text{10}\cdot \text{10}\cdot \text{10}$

10 6

$\text{826}\cdot \text{826}\cdot \text{826}$

826 3

$\text{3021}\cdot \text{3021}\cdot \text{3021}\cdot \text{3021}$

3021 4

$6\cdot 6\cdot 6\cdot \cdots \cdot 6$     (85 factors of 6).

6 85

$2\cdot 2\cdot 2\cdot \cdots \cdot 2$     (112 factors of 2).

2 112

For the next examples, expand the terms. (Do not find the actual values).

5 3

5 · 5 · 5

15 2

15 · 15

117 5

117 · 117 · 117 · 117 · 117

7 4

7 · 7 · 7 · 7

Determine the value of each of the powers.

3 2

9

1 2

1

15 2

225

3 4

81

1 4

1

7 3

343

Simplify as far as possible.

(2x) 3

2 3 · x 3 = 8x 3

302 0

1

(-2x) 3

(-2) 3 · x 3 = -8x 3

2 3 · 2 4

2 3+4 = 2 7

$\frac{{x}^{8}}{{x}^{3}}$

${x}^{8-3}={x}^{5}$

$\frac{\text{25}{x}^{2}}{{5x}^{8}}$

$\frac{\text{25}}{5}{x}^{2-8}={5x}^{-6}=\frac{5}{{x}^{6}}$

(3 -1 +2 -1 ) -1

$\frac{1}{{3}^{-1}+{2}^{-1}}=\frac{1}{\frac{1}{3}+\frac{1}{2}}=1\cdot \left(\frac{3}{1}+\frac{2}{1}\right)=3+2=5$

where we get a research paper on Nano chemistry....?
nanopartical of organic/inorganic / physical chemistry , pdf / thesis / review
Ali
what are the products of Nano chemistry?
There are lots of products of nano chemistry... Like nano coatings.....carbon fiber.. And lots of others..
learn
Even nanotechnology is pretty much all about chemistry... Its the chemistry on quantum or atomic level
learn
da
no nanotechnology is also a part of physics and maths it requires angle formulas and some pressure regarding concepts
Bhagvanji
hey
Giriraj
Preparation and Applications of Nanomaterial for Drug Delivery
revolt
da
Application of nanotechnology in medicine
what is variations in raman spectra for nanomaterials
ya I also want to know the raman spectra
Bhagvanji
I only see partial conversation and what's the question here!
what about nanotechnology for water purification
please someone correct me if I'm wrong but I think one can use nanoparticles, specially silver nanoparticles for water treatment.
Damian
yes that's correct
Professor
I think
Professor
Nasa has use it in the 60's, copper as water purification in the moon travel.
Alexandre
nanocopper obvius
Alexandre
what is the stm
is there industrial application of fullrenes. What is the method to prepare fullrene on large scale.?
Rafiq
industrial application...? mmm I think on the medical side as drug carrier, but you should go deeper on your research, I may be wrong
Damian
How we are making nano material?
what is a peer
What is meant by 'nano scale'?
What is STMs full form?
LITNING
scanning tunneling microscope
Sahil
how nano science is used for hydrophobicity
Santosh
Do u think that Graphene and Fullrene fiber can be used to make Air Plane body structure the lightest and strongest. Rafiq
Rafiq
what is differents between GO and RGO?
Mahi
what is simplest way to understand the applications of nano robots used to detect the cancer affected cell of human body.? How this robot is carried to required site of body cell.? what will be the carrier material and how can be detected that correct delivery of drug is done Rafiq
Rafiq
if virus is killing to make ARTIFICIAL DNA OF GRAPHENE FOR KILLED THE VIRUS .THIS IS OUR ASSUMPTION
Anam
analytical skills graphene is prepared to kill any type viruses .
Anam
Any one who tell me about Preparation and application of Nanomaterial for drug Delivery
Hafiz
what is Nano technology ?
write examples of Nano molecule?
Bob
The nanotechnology is as new science, to scale nanometric
brayan
nanotechnology is the study, desing, synthesis, manipulation and application of materials and functional systems through control of matter at nanoscale
Damian
Is there any normative that regulates the use of silver nanoparticles?
what king of growth are you checking .?
Renato
What fields keep nano created devices from performing or assimulating ? Magnetic fields ? Are do they assimilate ?
why we need to study biomolecules, molecular biology in nanotechnology?
?
Kyle
yes I'm doing my masters in nanotechnology, we are being studying all these domains as well..
why?
what school?
Kyle
biomolecules are e building blocks of every organics and inorganic materials.
Joe
Got questions? Join the online conversation and get instant answers!

#### Get Jobilize Job Search Mobile App in your pocket Now! By By OpenStax By Edgar Delgado By Ellie Banfield By OpenStax By OpenStax By OpenStax By Jill Zerressen By David Bourgeois By OpenStax